Higher rank quantum-classical correspondence - Hilgert, Joachim; Weich, Tobias; Wolf, Lasse Lennart (Analysis & PDE)
For a compact Riemannian locally symmetric space $Γ\backslash G/K$ of arbitrary rank we determine the location of certain Ruelle-Taylor resonances for the Weyl chamber action. We provide a Weyl-lower bound on an appropriate counting function for the Ruelle-Taylor resonances and establish a spectral gap which is uniform in $Γ$ if $G/K$ is irreducible of higher rank. This is achieved by proving a quantum-classical correspondence, i.e. a 1:1-correspondence between horocyclically invariant Ruelle-Taylor resonant states and joint eigenfunctions of the algebra of invariant differential operators on $G/K$.

Spectral correspondences for finite graphs without dead ends - Bux, Kai-Uwe; Hilgert, Joachim; Weich, Tobias (arXiv:2307.10876)
We compare the spectral properties of two kinds of linear operators characterizing the (classical) geodesic flow and its quantization on connected locally finite graphs without dead ends. The first kind are transfer operators acting on vector spaces associated with the set of non backtracking paths in the graphs. The second kind of operators are averaging operators acting on vector spaces associated with the space of vertices of the graph. The choice of vector spaces reflects regularity properties. Our main results are correspondences between classical and quantum spectral objects as well as some automatic regularity properties for eigenfunctions of transfer operators.

Spectral correspondences for rank one locally symmetric spaces: the case of exceptional parameters - Arends, Christian; Hilgert, Joachim (Journal de l’École polytechnique — Mathématiques)
In this paper we complete the program of relating the Laplace spectrum for rank one compact locally symmetric spaces with the first band Ruelle-Pollicott resonances of the geodesic flow on its sphere bundle. This program was started by Flaminio and Forni for hyperbolic surfaces, continued by Dyatlov, Faure and Guillarmou for real hyperbolic spaces and by Guillarmou, Hilgert and Weich for general rank one spaces. Except for the case of hyperbolic surfaces a countable set of exceptional spectral parameters always left untreated since the corresponding Poisson transforms are neither injective nor surjective. We use vector valued Poisson transforms to treat also the exceptional spectral parameters. For surfaces the exceptional spectral parameters lead to discrete series representations of $SL(2,\mathbb R)$. In higher dimensions the situation is more complicated, but can be described completely.
Keywords: Ruelle resonances; Poisson transforms; locally symmetric spaces; principal series representations

Spectral correspondences for rank one locally symmetric spaces - The case of exceptional parameters - Hilgert, Joachim; Arends, C. (J. de l'École polytechnique — Mathématiques)

Aspects of control theory on infinite-dimensional Lie groups and G-manifolds - Hilgert, Joachim; Glöckner, H. (J. Diff. Equations)

Open Educational Resources zur Förderung nachhaltiger Bildung und Forschung. In: Jahrestagung 2023 der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaften - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. The Teacher-Training-Platform on the SAFE Project Website - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. Administrative and financial information - Schneider, Jennifer Nicole

Green-4-Future – Project Insights to its best! In: Training and Cooperation Activity (TCA) “Green Erasmus: pathways to sustainable projects and institutions” - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA1. Business CANVAS Model – in Green Entrepreneurships - Schneider, Jennifer Nicole

Game Studies – Role Play in Therapy and Education. Pen and Paper Congress.Vortrag: Potenziale von Open Educational Resources bei Pen& Paper Rollenspielen in der Bildungspraxis nutzen! – Warum und wie soll das gehen?! - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA2. Creative Thinking – in Green Entrepreneurships - Schneider, Jennifer Nicole

STEMinAction- Final Project Meeting – Unlocking Long-Term Sustainability: Harnessing Open Educational Resources (OER) Beyond Project Lifetimes - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA1. Use, sharing and creating Open Educational Resources – Why is it so important? - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. The SAFE Learning Videos - Schneider, Jennifer Nicole

Gestaltung von Open Educational Resources zur Förderung von Nachhaltigkeit in Bildung und Wirtschaft - Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA1. Creative Thinking – in Green Entrepreneurships - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19 - Schneider, Jennifer Nicole

Intersektionalität und erzählte Welten : literaturwissenschaftliche und literaturdidaktische Perspektiven
Der vorliegende Band versammelt intersektionale literaturwissenschaftliche und -didaktische Fallstudien aus unterschiedlichen Philologien und bietet so ein Prisma der Erforschung literarischer Repräsentationen des Zusammenspiels von einander verschärfenden bzw. abschwächenden Diskriminierungskategorien. Die Einzelbeiträge präsentieren kritische Reflexionen und Modifizierungen verschiedener Positionen der intersektionalen Forschung sowie Beispiele für die vielfältige Ausgestaltung intersektional orientierter Textanalyse auf theoretischer und methodischer Ebene. Da wissenschaftliche und literarische ebenso wie zeitgenössische und historische Texte in verschiedenen Sprachen (Englisch, Deutsch, Italienisch, Niederländisch, Spanisch etc.) aufgegriffen werden, zeigt der Band auf, dass Machtstrukturen in unterschiedlichen kulturellen Kontexten Analogien aufweisen, deren Analyse von Differenzierungen verschiedener Herrschaftsstrukturen profitiert.

Intersektionalität und erzählte Welten
Intersektionalität hält als Forschungsgegenstand, als Schauplatz theoretischer Diskussion und als Analyseperspektive seit Jahren verstärkt Einzug in unterschiedliche akademische Disziplinen und Bereiche. Es verwundert daher nicht, dass sich das Intersektionalitätsparadigma auch im Bereich der Literaturwissenschaft und -didaktiken zunehmend als produktiv erweist, wie wir mit dem Sammelband zeigen wollen, der intersektionale literaturwissenschaftliche und -didaktische Fallstudien aus unterschiedlichen Philologien versammelt und so ein Prisma der Erforschung literarischer Repräsentationen des Zusammenspiels von einander verschärfenden bzw. abschwächenden Diskriminierungskategorien bietet. Inwiefern die Einzelbeiträge kritische Reflexionen verschiedener Positionen der Intersektionalitätsforschung präsentieren und Beispiele für die vielfältige Ausgestaltung intersektional orientierter Textanalyse auf theoretischer und methodischer Ebene anbieten sowie didaktische Lesarten des Intersektionalitätsparadigmas aufzeigen, machen wir aufbauend auf einer ausführlichen Begriffs- und Theoriereflexion einleitend deutlich.

A pairing formula for resonant states on finite regular graphs - Hilgert, Joachim; Arends, C.; Frahm, J.

Edge Laplacians and vector valued Poisson transforms for graphs - Hilgert, Joachim; Arends, C.; Frahm, J.

Quantization in fibering polarizations, Mabuchi rays and geometric Peter--Weyl theorem - Hilgert, Joachim; Baier, T.; Kaya, O.; Mourao, J.; Nunes, J.

Towards the Future of Multi-Layer Music Encoding: The IEEE 1599 v2.0 Draft - Baratè, Adriano; Haus, Goffredo; Ludovico, Luca A.; Mauro, Davide Andrea (2023 4th International Symposium on the Internet of Sounds)

Towards the Future of Multi-Layer Music Encoding: The IEEE 1599 v2.0 Draft - Baratè, Adriano; Haus, Goffredo; Ludovico, Luca A.; Mauro, Davide Andrea (2023 4th International Symposium on the Internet of Sounds)

Held*innenträume. Superheldinnen und Superhelden selbst erdacht - Paderborner Grundschulkinder werden auf die Begegnung mit Salah Naoura vorbereitet. - Kruse, Iris; Schäfer, Luisa Maria (Salah Naoura. Bielefelder Poet in Residence 2022. Paderborner Kinderliteraturtage 2022.)

Bewegtes Haus und bewegte Gedanken - Rezeptionsgedanken von Grundschulkindern zu Frau Susetts wundersame Reise. - Schäfer, Luisa Maria; Innhoff, Julia; Winter, Lys (Salah Naoura. Bielefelder Poet in Residence 2022. Paderborner Kinderliteraturtage 2022.)

Ruelle-Taylor resonances of Anosov actions - Hilgert, Joachim; Guedes Bonthonneau, Y.; Guillarmou, C.; Weich, Tobias

#SayTheirNames: Widerständige Medien der Erinnerung rechter Gewalt«, mit Sarah Horn - Degeling, Jasmin (feministische studien: Feministisches Erinnern)

Szenen kritischer Relationalität

Mediale und digitale Darstellungen des Immateriellen Kulturerbes während der Coronapandemie in Praxis und Forschung. Online-Umfragen und Podcast des Forschungsprojekts „Tradition im Wandel" - Leineweber, Jonas (Heimat in Europa - Themen der BHU 2021)
Fragen der medialen Darstellung des Immateriellen Kulturerbes sind zwar nicht neu, haben durch die Coronapandemie aber enorm an Bedeutung gewonnen. Dabei werden nicht nur die Trägergruppen und Akteurinnen und Akteure, sondern auch die sich mit dem Immateriellen Kulturerbe auseinandersetzenden Forschungsprojekte vor Herausforderungen gestellt. Wie können Untersuchungen ermöglicht werden, wenn der Zugang zum Feld durch zahlreiche Einschränkungen erschwert oder aufgrund von Absagen und Ausfällen nicht möglich ist? Wie lassen sich die Auswirkungen der Coronapandemie wiederum in Forschungsvorhaben einbinden und zum Gegenstand wissenschaftlicher Auseinandersetzungen machen? Und schließlich: Wie können die Forschungsergebnisse niederschwellig vermittelt und in Interaktion mit den Trägergruppen diskutiert und perspektiviert werden, wenn klassische Informationsangebote wie Vortrags- und Workshopformate pandemiebedingt nicht stattfinden können? Mit diesen Fragen sah sich das seit 2016 laufende Forschungsprojekt „Tradition im Wandel – Das Schützenwesen in Westfalen als Immaterielles Kulturerbe“ während der Coronapandemie konfrontiert.
Keywords: Immaterielles Kulturerbe; Bräuche; Rituale; Feste; Medien; digital

Immaterielles Kulturerbe praxisnah erforschen. Das Forschungsprojekt „Tradition im Wandel“ – Schützenwesen in Westfalen - Leineweber, Jonas; Becker, Peter (Bürger Schützen Borken 1323 – 2023 (Katalog der Ausstellung vom 12.08.2023 – 11.02.2024 im Forum Altes Rathaus Borken))

Szenen kritischer Relationalität

Infrastructure’s Distribution of Sensibilities: On Counter / Documentation, Attachment, and the Possibility of a Poetics of Infrastructure - Degeling, Jasmin (Infrastructures of Sense|Making – Techniques, Powers, Operations)

Jenny Schrödl, Eike Wittrock (Hg.): Theater* in queerem Alltag und Aktivismus der 1970er und 1980er Jahre - Degeling, Jasmin (MEDIENwissenschaft: Rezensionen | Reviews)

Fast Convergence of Inertial Multiobjective Gradient-like Systems with Asymptotic Vanishing Damping - Sonntag, Konstantin; Peitz, Sebastian (arXiv:2307.00975)
We present a new gradient-like dynamical system related to unconstrained convex smooth multiobjective optimization which involves inertial effects and asymptotic vanishing damping. To the best of our knowledge, this system is the first inertial gradient-like system for multiobjective optimization problems including asymptotic vanishing damping, expanding the ideas laid out in [H. Attouch and G. Garrigos, Multiobjective optimization: an inertial approach to Pareto optima, preprint, arXiv:1506.02823, 201]. We prove existence of solutions to this system in finite dimensions and further prove that its bounded solutions converge weakly to weakly Pareto optimal points. In addition, we obtain a convergence rate of order O(t−2) for the function values measured with a merit function. This approach presents a good basis for the development of fast gradient methods for multiobjective optimization.

Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Bernreuther, Marco; Dellnitz, Michael; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Sonntag, Konstantin; Volkwein, Stefan (arXiv:2308.01113)
Multiobjective optimization plays an increasingly important role in modern applications, where several criteria are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. The advances in algorithms and the increasing interest in Pareto-optimal solutions have led to a wide range of new applications related to optimal and feedback control - potentially with non-smoothness both on the level of the objectives or in the system dynamics. This results in new challenges such as dealing with expensive models (e.g., governed by partial differential equations (PDEs)) and developing dedicated algorithms handling the non-smoothness. Since in contrast to single-objective optimization, the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging, which is particularly problematic when the objectives are costly to evaluate or when a solution has to be presented very quickly. This article gives an overview of recent developments in the field of multiobjective optimization of non-smooth PDE-constrained problems. In particular we report on the advances achieved within Project 2 "Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Switches, State Constraints and Model Order Reduction" of the DFG Priority Programm 1962 "Non-smooth and Complementarity-based Distributed Parameter Systems: Simulation and Hierarchical Optimization".

Gelingensbedingungen für den Einsatz digitaler Medien in Lernsituationen in der Grundschule im Bereich Lesen – Befunde einer qualitativen Befragung von Lehrpersonen - Lorenz, R.; Brüggemann, T. U.; Eickelmann, Birgit; McElvany, N. (Jahrbuch für Schulentwicklung)

Neuartige Flugstrom SCR an online synthetisierten, nanoskaligen Katalysatorpartikeln in einem kombinierten Gasreinigungsprozess (Poster) - Beimdiek, Janis; Schiller, Sascha; Schmid, Hans-Joachim

Investigations on Aerosol Synthesis of Polymer Particles - Elma, Benjamin; Beimdiek, Janis

Deutsch für den Beruf [Sammelrezension] Sander, Isa-Lou; Efing, Christian (Hrsg.): Der Betrieb als Sprachlernort. Tübingen: Narr Francke Attempto, 2021 (Kommunizieren im Beruf, 4). -- ISBN 978-3-8233-8442-7. 264 Seiten, € 68,00. Tichy, Ellen; Tesch, Felicitas (Hrsg.): Deutsch in Fach und Beruf. Aktuelle Fragen und neue Ansätze der Fremdsprachenvermittlung. Berlin: Peter Lang, 2021 (Berufssprache Deutsch in Theorie und Praxis, 2). -- ISBN 978-3-631-79553-8. 194 Seiten, € 49,95. Niederhaus, Constanze: Deutsch für den Beruf. Eine Einführung. Berlin: Erich Schmidt, 2022 (Grundlagen Deutsch als Fremd- und Zweitsprache, 4). -- ISBN 978-3-503-20545-5. 265 Seiten, € 22,00. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

Curriculare Überlegungen zum fach- und berufsorientierten Deutsch - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

Curriculumkompetenz - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

DaF-Übungsfirma - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

Globale Simulation - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

Fallstudie - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

Planspiel - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

DaF und DaZ im Kontext Deutsch für den Beruf: Schnittstellen und Divergenzen - Niederhaus, Constanze; Prikoszovits, Matthias (Deutsch als Fremdsprache)

"DAS iSt STRASSEN-PoLiTiK!" Politisches "meaning making" im Szene-Graffiti - Tophinke, Doris (Kunst und Politik)

From mental models to algorithmic imaginaries to co-constructive mental models - Schulz, Christian (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)